Scopic Regimentation of Cuban Popular Religious Altars - Kristina Wirtz (Semiotic Review, 2021)
Cuban popular religious altars command attention with their elaborate presentations of statues, dolls, figurines, photographs, vessels, and offerings to a host of spirits and saints. The altar is cosmogenic: any given altar in all of its inventive particularity is a diagram that figures a world of relations between the living practitioner and the constellation of spirits who work with that practitioner. The concept of scopic regimentation, adapted from what Christian Metz (1975) and Martin Jay (1988) call the scopic regime, describes how the location, arrangement, and qualities of altars and their objects dynamically figure possibilities and tensions in developing spiritual relationships. Four dimensions of the altar’s work of scopic regimentation are described. First is the altar’s work as a prism, in which the altar’s objects refract general spiritual presence into distinct spirit figures. Second, the altar’s arrangement as a constellation diagrams multiple, complex relationalities among spirits as an image of the evolving spiritual biography of the altar’s owner. Third, the altar’s work as interface shapes multimodal communicative engagements between spirits and religious adherents. And fourth, the altar serves as an aperture in diagramming the limits of knowledge about spirits in its play between revelation and concealment.